Factors to heighten success of ball acquisition in kick-off and 50m restart kick play in rugby football - Nakagawa, A.; Hirose, K. (International Journal of Sport & Health Science, 2007)
The objective of this research is to clarify the factors to heighten success of ball acquisition in kick-off and 50m restart kick (KO) play from the view point of the kicking side. For that purpose, the process of ball acquisition of the kicking side was divided into three play elements: the kick, the contest for the ball, and the prompt ruck/maul formation after KO. A total of 448 KO plays in 43 world class matches were taken as samples and correlation between performance in each play element and ball acquisition rate of the kicking side was quantitatively analyzed. It can be concluded from the results of analysis as follows: 1) In order to increase the success rate of ball acquisition in KO play with respect to the kicking side, an important factor is for the kicking side to take some action against the ball earlier than the opponent at an aerial contest for the ball. 2) In order to realize it, an important factor is to create situations where the receiving side cannot employ the lifting play. It is also implied that in field practice, an effective way to improve the performances in KO play is to devise tactics and to have players achieve a mastery of techniques to realize the factors to heighten success of ball acquisition in KO play which have been made clear in this research.